CRISPR/Cas9 Genome Editing for Enhancing Lentil Resistance to Fungal Diseases (Journal of the Bangladesh Agricultural University, 2025)
Lentil (Lens culinaris Medik.) is a nutritionally and economically vital legume crop cultivated globally. However, its productivity is severely threatened by fungal diseases such as Stemphylium blight, Fusarium wilt, and Ascochyta blight. Traditional breeding and chemical control strategies have shown limited success in providing long-term resistance against these pathogens. The advent of CRISPR/Cas9 genome editing offers a revolutionary and targeted approach to enhance disease resistance in lentils by enabling precise modification of key genes. This review highlights the mechanism of CRISPR/Cas9 and its application in lentil improvement, with particular focus on editing susceptibility (S) genes such as Lc07593, LcMLO, and LcSWEET13, which facilitate pathogen infection, and modulating genes in defense signaling pathways like LcNPR1, LcEDS1, and LcMYC2. Furthermore, the potential of engineering pattern recognition receptors (PRRs) like FLS2, EFR, and CERK1 for improved pathogen detection is discussed. The integration of CRISPR with speed breeding and marker-assisted selection further accelerates the development of resistant cultivars. Despite current challenges in transformation efficiency and regulatory barriers, CRISPR/Cas9 presents a promising tool for sustainable lentil disease management. Future directions include multiplex editing, base/prime editing, and epigenome modulation for fine-tuned resistance, all contributing to a resilient and high-yielding lentil crop.J Bangladesh Agril Univ 23(2): 148-156, 2025